1997
DOI: 10.1002/hep.510250437
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic expression of hepatitis C virus structural proteins in the mouse

Abstract: lies. 3,4 In general, the genome is flanked in its 5 -untranslated Although hepatitis C virus (HCV) is a leading cause region by a highly conserved (ú98%) 341 nucleotide seof morbidity and mortality worldwide, the role of viral quence, which appears to play a key role in translational cytopathic effects remains unclear. To study the biosyncontrol. 1,5,6 The coding region encodes structural proteins in thesis of HCV structural proteins and their pathogenic its N-terminal portion that include a nonglycosylated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
1
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 9 publications
0
85
1
2
Order By: Relevance
“…2 We used the albumin promoter as did Lerat et al 9 The transgenic mice developed by Kawamura et al demonstrated high core expression, 2 whereas those by Lerat et al showed much lower core protein expression, suggesting that levels of core protein expression alone do not explain the HCC phenotype, and that the FVB background may have a protective role in hepatocarcinogenesis. Indeed, saline-treated control animals expressing the core and core-E1-E2 construction on the FVBϫC57Bl/6 background both failed to develop HCC, unless they were exposed to a chemical carcinogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 We used the albumin promoter as did Lerat et al 9 The transgenic mice developed by Kawamura et al demonstrated high core expression, 2 whereas those by Lerat et al showed much lower core protein expression, suggesting that levels of core protein expression alone do not explain the HCC phenotype, and that the FVB background may have a protective role in hepatocarcinogenesis. Indeed, saline-treated control animals expressing the core and core-E1-E2 construction on the FVBϫC57Bl/6 background both failed to develop HCC, unless they were exposed to a chemical carcinogen.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, more recently, Moriya et al developed a transgenic mouse model on the C57Bl/6 background that overexpresses HCV core protein under the control of the HBV enhancer that is capable of inducing HCC in a subset of animals following the development of steatosis. [3][4][5][6] These apparently contradictory findings could be due to inherent differences in the transgenes, HCV core dose effect, mouse genetic background, or a combination of these.…”
Section: H Epatitis C Virus (Hcv) Infects An Estimated 170mentioning
confidence: 99%
“…127 These contradictory findings may be due to the young age at which the livers were analysed (up to 6 months), since neoplasms were not observed in mice younger than 13 or 16 months in the studies reported by Lerat et al and Koike et al,respectively. 124,126 However, a different study by Pasquinelli et al also observed "no significant liver injury" in transgenic mice expressing HCV core protein up to 18 months of age.…”
Section: Hepatitis C Core Proteinmentioning
confidence: 95%
“…At the same time, co-infection increases the persistence of HCV infection and, subsequently, the risk of developing liver disease 30 . As several studies have suggested, liver damage is related mainly to immune mediated mechanisms, with the stimulation of cytotoxic T cell (CTL) response against hepatocytes infected with HCV 9,10,20,32 . This response would lead to hepatocyte lysis and consequent increased release of liver transaminases in plasma.…”
mentioning
confidence: 99%